Internal Medicine Clerkship Amidst COVID-19 Pandemic: A Cross-Sectional Study of the Clinical Learning Experience of Undergraduate Medical Students at Makerere University, Uganda - Bongomin, Felix; Olum, Ronald; Nakiyingi, Lydia; Lalitha, Rejani; Ssinabulya, Isaac; Sekaggya- Wiltshire, Christine; Ocama, Ponsiano; Byakika-Kibwika, Pauline (Advances in Medical Education and Practice, 2021)
The coronavirus-2019 (COVID-19) pandemic continues to impose a significant impact on medical education. We aimed to describe the clinical learning experience of undergraduate medical students undertaking internal medicine clerkship during the COVID-19 pandemic at Makerere University, Uganda. Methods: A descriptive, cross-sectional study among medical students in clinical years of study pursuing the Bachelor of Medicine and Bachelor of Surgery undergraduate degree program was conducted in November 2020. Only 3rd (junior clerks) and 5th (senior clerks) year medical students whose internal medicine clerkships were interrupted by the COVID-19 pandemic were studied. Results: Data of 188 (95%) eligible clinical year students; junior (101, 54.0%) and senior (86, 46.0%) were analysed. Median age was 24 (range: 22–42) years. Majority (70.1%) were male and Ugandan nationals (94.1%). Sixty-four (30.3%) students reported inadequate personal protective equipment, 152 (81.7%) felt at risk of contracting COVID-19, and 127 (67.9%) said it was difficult to observe COVID-19 standard operating procedures. Twentytwo students (11.9%) were discouraged from pursuing a career in internal medicine. Overall, most students reported good or excellent clinical experience pre-COVID-19 era compared to during the COVID-19 era (4.0 vs 3.5, p<0.0001). Senior clerks significantly believed that the time allocated for the rotation was adequate (p<0.0001) and they were able to complete their study objectives (p<0.001), compared to the junior clerks. Senior clerks believed that learning was difficult when combined with junior clerks (p=0.013). About half of the students (51.4%, n=95) reported clinical teaching should remain as it was in the pre- COVID-19 era. Conclusion: The COVID-19 pandemic has had a significantly negative effect on the clinical learning experience of the students. There is need to review the current teaching and learning methods to suit teaching and learning during pandemics of highly infectious diseases to ensure safe and effective learning experience.
Keywords: Clinical learning experience; COVID-19; Internal medicine; Makerere University